Arm coordination and intracyclic velocity variations during a time limit test at the velocity of VO2max - Morais, P.; Ribeiro, J.; Balonas, A.; Figueiredo, P.; Seifert, L.; Chollet, L.; Keskinen, K. L.; Vilas-Boas, J. P.; Fernandes, R. (Archivos de medicina del deporte, 2008)
In swimming, the index of coordination (IdC), initially proposed by Chollet, et al. (2000), measures the lag time between the end of the propulsive phase of one arm and the beginning of the propulsive phase of the opposite arm. Since then, few studies have been conducted using protocols with an imposed constant pace until exhaustion. The purpose of the present study was to assess the modifications of arm coordination during a Time Limit test (to exhaustion) at the minimum velocity of VO2max (TLim-vVO2 max). Additionally, knowing that the magnitude of the intracyclic velocity variations has been considered as an indicator of swimming efficiency, it was studied the relationship between this parameter and the IdC during the TLim-vVO2 max test. Three high level male swimmers were studied (181±12cm, 75±11kg and a VO2-max of 74±4 ml.kg-1.min-1). The vVO2max was determined through an intermittent incremental protocol and, 48h later, the TLim-vVO2max test was conducted according with Fernandes, et al. (2003). Velocity was always controlled using a visual pacer and VO2 was measured through direct oximetry (K4 b2 , Cosmed, Italy) using a respiratory snorkel and valve system. Video analysis was used in order to assess the IdC to evaluate the arm coordination (Chollet, et al. , 2000). The APAS software (Ariel Dynamics Inc, USA) was used to assess the horizontal intracyclic velocity variations of the centre of mass: 4 complete cycles were analyzed (one in the first, another in the last 50m, and two in the intermediate 100m) of the TLim-vVO2max test. Mean (SD) and Spearman correlation coefficient were used (p<0.05). As it is possible to observe in Figure 1, the IdC reveals some stability during the TLim-vVO2max test in the swimmers 1 and 2 and seems to change in swimmer 3, being in accordance with the data obtained by Alberty, et al. (2008). Furthermore, the IdC during TLim-vVO2max seems to be inversely related with the intracyclic velocity variations of the CM (-0.99, -0.78, -0.78 and -0.64 for subjects #1, 2, 3 and total sample, respectively). These results seem to express that the swimmers, to be able to maintain the vVO2max, adapt their arm coordination. These adaptations, and the lower values of intracyclic velocity variations, seem to be a strategy to deal with the appearance of fatigue in the last moments of the time to exhaustion test. The IdC seem to reflect the effects of exercise to exhaustion on swimming technique, being a useful tool for coaches and scientists in order to better understand the technique modifications under fatigue conditions. As suggested before (Figueiredo, et al., 2008), changes on arm coordination, linked to muscular endurance limitations, appear to be a compensatory mechanism used by swimmers, trying to find the most efficient arm coordination for a particular context